Hepatitis E in the pediatric population: An overlooked disease but a genuine concern? - Janczura, Jakub; Jończyk, Kamil; Nowak, Klaudia; Choromański, Tymon; Pawliński, Jakub; Starnawski, Piotr; Woynarowski, Marek (Clinical and Experimental Hepatology, 2025)
Hepatitis E virus (HEV) is a significant yet underdiagnosed cause of acute and chronic hepatitis, particularly in pediatric populations. While HEV infection in children is often asymptomatic or mild, it can progress to severe outcomes in immunocompromised patients, such as organ transplant recipients or those undergoing chemotherapy. HEV genotypes 1 and 2 are predominantly responsible for waterborne outbreaks in endemic regions, whereas genotypes 3 and 4 are associated with zoonotic transmission in developed countries. Emerging evidence also links HEV to extrahepatic manifestations, including neurological, renal, hematological, and pancreatic complications. Diagnosis remains challenging due to frequent asymptomatic presentation and limitations in serological testing, highlighting the importance of polymerase chain reaction (PCR)-based detection. Although vaccination shows promise, especially in endemic areas, its availability remains limited for pediatric populations. Addressing research gaps and improving surveillance, prevention, and treatment strategies are critical for reducing HEV-related morbidity in children.